The Urgency of Morals and Religion in Modern Society: Philosophical Perspectives - Salis Abdalah Hatami; Mulyana Mulyana (Gunung Djati Conference Series, 2022)
This article aims to discuss the urgency of morality and religion in the life of today's society. This research is a type of qualitative research that applies literature study. Here the author collects data from books and journals that are relevant to the research title. The findings and discussion of this research include the notion of morality and religion and the changes that become the urgency of morality and religion in life from a philosophical point of view. This study concludes that people's lack of belief in God and religion which causes neglect of their function has resulted in the scattering of moral values, even God and religion tend to be considered as obstacles to the progress of human life. Religion is considered useless or useful, so that morality built on the basis of religion must be marginalized from creativity and human life activities. This study recommends for further research on the urgency of morality and religion from various perspectives.